Analisis Sistem Antrian Di PT. Bank Negara Indonesia (Persero) Tbk. Kantor Cabang Manado - Ripit Budiman; Djoni Hatidja; Marline S Paendong (Sam Ratulangi University, 2020)
The purpose of this research was to determine the queuing model and determine the characteristic length of the queue at PT. Bank Negara Indonesia Branch Office of Manado. Data collection was carried out for 5 days. The queuing system model used is the B:M/M/S Model (Multiple Channel Query System), the number of tellers that operating there are 7 tellers and the service used is First Come First Served, the arrival rate is Poisson distribution, and the service time is Exponential distribution. The result of this research shows the average number of arrivals is 42 customers who come per hour, and the average number of customers served is 9 customers served per hour. There are no customers in the 0.01 system, the average number of customers in the system is 6 customers, the time customers spend in the queue and is being served is 8-9 minutes, the average number of customers waiting in the queue to be served is 1 customer, and the average time of customers spend for waiting in the queue is 1-2 minutes.